LIBRARIAN BELARUS. PROGRAM PRESS RELEASE OF SCIENTIFIC AND EDUCATIONAL TRIP - Perepelitsa, Iryna (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
In the scientific article the main libraries of Belarus are considered, which form the library system of a country, brief but substantial information about the features of their creation and functioning is presented.